Fatal mumps nephritis and myocarditis - Kabakus, N; Aydinoglu, H; Yekeler, H; Arslan, IN (Oxford Univ Press, 1999)
The case of a 14-year-old girl with fatal interstitial nephritis and myocarditis as complications of mumps is reported, The illness began with parotitis; renal symptoms developed within a week. The patient's renal and cardiac status and clinical course rapidly deteriorated and the outcome was fatal. The post-mortem renal biopsy sample showed interstitial mononuclear cell infiltration, oedema, and focal tubular epithelial damage in biopsy material of kidney, confirming the clinical diagnosis. Myocarditis was determined by electrocardiographic and echocardiographic findings. Since it has been reported that fatal complications such as myocarditis, dilated cardiomyopathy, and nephritis may develop in the course of mumps, the patients with mumps, especially in complicated cases, should be followed closely because of the severe clinical conditions which may progress.